Infant Feeding Practices, Health And Nutritional Status: A Prospective Study Of Infants Seen At The University Of Malaya Medical Centre, Kuala Lumpur - Chong, Mei Chan (2003)
Feeding practices during infancy are important determinants of a baby's future physical and mental well being because of the rapid growth spurts and development of organ and tissues during the first year of life. Hence the purpose of this study was to determine the relationship between infant feeding practices and the health status of infants below six months of age. A prospective study was carried out to examine the relationship between infant feeding and the health status of infants in the first six months of life at the University of Malaya Medical Centre Kuala Lumpur. A total of 1 50 newborns from the medical centre were selected and fol lowed up for six months. Feeding practices were assessed monthly by questionnaire, frequency and duration of illnesses were recorded and anthropometric measurements were taken during monthly visits to the child health clinic.